Properties of acyl modified poly(glycerol‐adipate) comb‐like polymers and their self‐assembly into nanoparticles. Issue 20 (8th July 2016) - Taresco, Vincenzo; Suksiriworapong, Jiraphong; Creasey, Rhiannon; Burley, Jonathan C.; Mantovani, Giuseppe; Alexander, Cameron; Treacher, Kevin; Booth, Jonathan; Garnett, Martin C.
ABSTRACT: There is an increasing need to develop bio‐compatible polymers with an increased range of different physicochemical properties. Poly(glycerol‐adipate) (PGA) is a biocompatible, biodegradable amphiphilic polyester routinely produced from divinyl adipate and unprotected glycerol by an enzymatic route, bearing a hydroxyl group that can be further functionalized. Polymers with an average Mn of ∼13 kDa can be synthesized without any post‐polymerization deprotection reactions. Acylated polymers with fatty acid chain length of C4, C8, and C18 (PGAB, PGAO, and PGAS, respectively) at different degrees of substitution were prepared. These modifications yield comb‐like polymers that modulate the amphiphilic characteristics of PGA. This novel class of biocompatible polymers has been characterized through various techniques such as FT‐IR, 1 H NMR, surface, thermal analysis, and their ability to self‐assemble into colloidal structures was evaluated by using DLS. The highly tunable properties of PGA reported herein demonstrate a biodegradable polymer platform, ideal for engineering solid dispersions, nanoemulsions, or nanoparticles for healthcare applications. © 2016 The Authors. Journal of Polymer Science Part A: Polymer Chemistry Published by Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3267–3278 Abstract : The pendant‐side hydroxyl moiety of poly(glycerol‐adipate) (PGA) was acylated with a set of fatty acids of chain length C4, C8, and C18 (PGAB, PGAO, and PGAS, respectively) at different degrees of grafting. These modifications yielded comb‐like polymers that modulated the hydrophilic–hydrophobic balance of PGAx. The length of the fatty ester side‐chains and degree of substitution considerably affected the physicochemical properties of the resulting polymers and their ability to form nanoparticles.